Coping Strategy Enhancement for Families Who Have Children with Thalassemia Through Family Counseling at Sukabumi Thalassemia Foundation - Meiti Subardhini; Rini Hartini Rinda A; Elin Herlina (Asian Social Work Journal, 2019)
Family copyng strategy is one of the factors so that families with thalassemia children can survive and function properly. The purpose of this study is to determine whether family counseling had an effect on improving family copyng strategy, by identifying 1). What are the characteristics of children and families in the Sukabumi branch thalassemia foundation? 2). What is the process of family counseling? 3). What are the results of implementing family counseling? This study used a qualitative approach with the action research method. Three families with thalassemia children with main data collection techniques by providing indeepth interview, supplemented by observations and study documentation. The results showed that children with thalassemia had transfused between 3 to 10 years, and routinely performed transfusions every week to every month. Family counseling provides solutions to problems faced by families as an effort to improve family strategy copyng. Active families seek support from extended families, doctors and friends. Families always think positively and organize themselves not to display negative emotions and improve spiritual life. The conclusion of this study indicates that family counseling can have a positive influence on improving family copyng strategy. Family counseling as an intervention that involves all family members also strengthen relationships between family members. The practical implication of the family counseling process requires commitment from all family members, the willingness to openly convey what is felt and thought.